Los alimentos según el código orgánico de la niñez y adolescencia en el derecho positivo ecuatoriano - Landívar Rosales, Rosa Amelia (2014)
The Organic Code of Childhood and Adolescence entered into force by Law 100, published in Official Gazette No. 737 of January 3, 2003, which repealed the Juvenile Code and regulates the right to food of children and adolescents and adults than those listed in Art 128 of the Code first invoked. This code is inspired by Organic Law on Freedom enshrined in Art 66 paragraph 2 of the Constitution of the Republic of Ecuador, which provides "The right to a decent life, to ensure the health, food and nutrition..." Being as it is the Constitution of the Republic of Ecuador, guarantor of rights, makes mothers having children, resorting to the Specialized Courts for Children and Adolescents, to ask for the effective protection via food demand their spouses, partners and former partners, in order to receive them monthly alimony, based on the full exercise of the same, and enjoy and enjoy a safe and healthy environment where they can be physical, psychological , emotional and intellectually developed, as it provides the same Code on Children and Adolescents. Additionally, as stated in the recital above, that is, who missed the obligors mentioned (spouses, partners and former partners), you must comply with the pointed in section 129 of the Code of Childhood and Adolescence, by positioning the proposed legal effect to the following bound on the provision of food, in order of priority given in the last paragraph of that provision , as follows: first the father and mother, even in cases of limitation, suspension or deprivation of witness against country, secondly the brothers who have turned eighteen and are not included in paragraphs 2 and 3 of Article 128 of the same Code, and finally fourth uncles. The problem arises in so far, although there is the Constitution of the Republic of Ecuador, as guarantor of rights and the same Code on Children and Adolescents, which determines the procedure for fixing a provisional pension food, the fact remains that the National Judicial Council in charge of the administrative side regarding the administration of justice plays a fundamental role in Haste administration of Justice, by creating more specialized courts, to with the opportunity to meet the case merits the user area, having performed in many cases the lack of clearance for fixing the defense and conciliation hearing the trial of foods mentioned in article 137 of the Code of Childhood and Adolescence judges given the volume of work have positioned or pointed diligence said after six months or one year of submission of the demand for food.